Antioxidant Effect of Standardized Extract of Propolis (EPP-AF®) in Healthy Volunteers: A “Before and After” Clinical Study - Diniz, Débora P. (Evid Based Complement Alternat Med, 2020)
BACKGROUND: Propolis is rich in polyphenols, especially flavonoids and phenolic acids, and has significant antioxidant activity, shown mainly in “in vitro” studies. OBJECTIVE: The aim of this study was to evaluate the antioxidant efficacy and safety of a standardized propolis extract in healthy volunteers. DESIGN: A two-phase sequential, open-label, nonrandomized, before and after clinical trial. METHODS: Healthy participants received two EPP-AF® doses (375 and 750 mg/d, P.O, tid) during 7 ± 2 days, starting with the lower doses. Immediately before starting EPP-AF® administration and at the end of each 7-day dosing schedule, blood and urine samples were collected for quantification of 8-OHDG (8-hydroxydeoxyguanosine) and 8-ISO (8-isoprostanes) in urine and GSH (reduced glutathione), GSSG (oxidized glutathione), SOD (superoxide dismutase), FRAP (Ferric Reducing Antioxidant Power), vitamin E, and MDA (malondialdehyde) in plasma. RESULTS: In our study, we had 34 healthy participants (67.7% women, 30 ± 8 years old, 97% white). The 8-ISO, a biomarker of lipid peroxidation, decreased with both doses of EPP-AF® compared to baseline (8-ISO, 1.1 (0.9–1.3) versus 0.85 (0.75–0.95) and 0.89 (0.74–1.0), ng/mg creatinine, P < 0.05, for 375 and 750 mg/d EPP-AF® doses versus baseline, mean and CI 95%, respectively). 8-OHDG, a biomarker of DNA oxidation, was also reduced compared to baseline with 750 mg/d doses (8-OHDG, 15.7 (13.2–18.1) versus 11.6 (10.2–13.0), baseline versus 750 mg/d, respectively, ng/mg creatinine, P < 0.05). Reduction of biomarkers of oxidative stress damage was accompanied by increased plasma SOD activity (68.8 (66.1–73.3) versus 78.2 (72.2–80.5) and 77.7 (74.1–82.6), %inhibition, P < 0.0001, 375 and 750 mg/d versus baseline, median and interquartile range 25–75%, respectively) and by increased GSH for 375 mg/d EPP-AF® doses (1.23 (1.06–1.34) versus 1.33 (1.06–1.47), μmol/L, P < 0.05). CONCLUSION: EPP-AF® reduced biomarkers of oxidative stress cell damage in healthy humans, with increased antioxidant enzymatic capacity, especially of SOD. This trial is registered with the Brazilian Registry of Clinical Trials (ReBEC, RBR-9zmfs9).